74.6k views
3 votes
Help !!!
See question in image.
Please show workings .


Help !!! See question in image. Please show workings . ​-example-1
User Smartboy
by
5.5k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

Given f(x) then the derivative f'(x) is

f'(x) = lim( h tends to 0 )
(f(x+h)-f(x))/(h)

= lim( h to 0 )
(x+h+(1)/(x+h )-(x+(1)/(x) ) )/(h)

= lim(h to 0)
(x+h+(1)/(x+h)-x-(1)/(x) )/(h)

= (lim(h to 0)
(h+(1)/(x+h)-(1)/(x) )/(h)

= lim( h to 0 )
(hx(x+h)+x-(x+h))/(hx(x+h))

= lim( h to 0 )
(hx(x+h)+x-x-h)/(hx(x+h))

= lim(h to 0 )
(hx(x+h))/(hx(x+h)) -
(h)/(hx(x+h))

Cancel the numerator/denominator of first fraction and h in the second

= lim ( h to 0 ) 1 -
(1)/(x(x+h)) ( let h go to zero ), then

f'(x) = 1 -
(1)/(x^2)

User Will Buck
by
5.1k points